(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the safety of clopidogrel in ischemic heart disease patients simultaneously suffering from cirrhosis with upper G bleed. Study Design: A randomized controlled trial study. Place and Duration of Study: This study was conducted at the Department of General Medicine of Nishtar Hospital Multan from August 2018 to May, 2019. Materials and Methods: Fifty two patients were equally divided into two groups; control group which received no antiplatelet drug and clopidogrel group in which group patients were prescribed clopidogrel at 75mg daily dose. All the patients were discharged on medication and were followed for a minimum of six months. Age, gender, underlying comorbidities including diabetes mellitus, hypertension, ischemic stroke and dyslipidemias, and incidence of upper GI bleed were compared between the two groups. Student’s t test and Chi square test were applied accordingly. P ≤0.05 was considered statistically significant. Results: Age, gender distribution and history of comorbidities including ischemic stroke, hypertension, diabetes mellitus and dyslipidemias were not significantly different between the two groups (p>0.05). Till the end of study, upper gastrointestinal bleeding was reported in 5 (19.2%) patients of the control group while it was reported in 12 (46.1%) patients of clopidogrel group and the difference in the outcome was statistically significant (p=0.039). Conclusion: There was significantly greater occurrence of upper GI bleed among the patients taking clopidogrel during the study duration whereas less number of patients from the control group presented with upper GI bleed.